Digital transformation in accounting - Busulwa, Richard, 1980-; Evans, Nina (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Digital Transformation in Accounting is a critical guidebook for accountancy and digital business students to navigate the effects of digital technology advancements, digital disruption and digital transformation on the accounting profession. Drawing on the latest research, this book: Unpacks dozens of digital technology advancements, explaining what they are and how they could be used to improve accounting practice Discusses the impact of digital disruption and digital transformation on different accounting functions, roles and activities Integrates traditional accounting information systems concepts and contemporary digital business and digital transformation concepts Includes a rich array of real-world case studies, simulated problems, quizzes, group and individual exercises as well as supplementary electronic resources. Provides a framework and a set of tools to prepare the future accounting workforce for the era of digital disruption. This book is an invaluable resource for students on accounting, accounting information systems and digital business courses, as well as accountants, accounting educators, and accreditation / advocacy bodies"--
Introduction and need for this book -- IT, information systems, strategic information systems, and digital technologies -- Digital technology advancements and digital disruption: game-changing opportunities and existential threats -- Digital business, the digital business imperative, and digital business transformation -- Digital disruption and digital transformation of accounting -- Impact of digital disruption and digital transformation on accountants -- The role of accountants in digital transformation strategy, digital business strategy, digital learning, adaptability and agility -- Role of Accountants in digital customer engagement, digital stakeholder engagement, and digital customer experience -- Role of accountants in enterprise architecture, technology sourcing, data analytics, and data management -- Role of accountants in security, information privacy, and digital ethics -- Role of accountants in digital leadership, accelerated change and transformation, digital risk management, and digital governance -- Keeping up with digital technologies -- Data Management, Data Analytics and Data Science Technologies -- Internet of Things Technologies -- Artificial Intelligence Technologies -- Video analytics, computer vision, and virtual reality technologies -- Robotics, drones and 3D/4D printing technologies -- Network and connectivity technologies -- Blockchain and distributed ledger technologies.
OCLC-licensed vendor bibliographic record.
Keywords: Accounting -- Data processing; Accounting -- Computer programs; Computer software -- Accounting; Information storage and retrieval systems -- Accounting; BUSINESS & ECONOMICS / Accounting / General; BUSINESS & ECONOMICS / International / Accounting; BUSINESS & ECONOMICS / Economics / General